Thalamic Metabolism and Restless Legs Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
Researchers at University of Bologna, Italy, evaluated medial thalamus metabolism and structural integrity in 23 patients with restless legs syndrome and 19 healthy controls.